Modified multi-walled carbon nanotube, flame-retardant PET (polyethylene terephthalate) material and preparation method of flame-retardant PET material

The carboxyl group amount of multi-wall carbon nanotubes is increased by two-step acid mixing treatment, which solves the problems of structural damage and insufficient flame retardant performance. It is applied in PET materials, which significantly improves flame retardant and impact performance, and avoids secondary fires. and the problem of reduced strength.

CN119241913APending Publication Date: 2025-01-03CHUZHOU GEMEITE TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411509155.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In the prior art, the acidification treatment of multi-wall carbon nanotubes leads to structural damage, the carboxyl group amount is small, which affects the flame retardant and mechanical properties of the material. The phosphorus-containing flame retardant decomposes at high temperature to produce toxic gases, and there is a secondary fire. Risk: PET materials have poor impact performance and the introduction of tougheners will reduce strength.

Method used

Using a two-step acid mixing treatment method, the modified multi-wall carbon nanotubes were prepared by mixing 98% sulfuric acid and 68% nitric acid, combined with H2O2, ultrasonic oscillation and reflux, which significantly improved the carboxyl grafting rate of multi-wall carbon nanotubes, and prepared modified multi-wall carbon nanotubes. Included in PET materials to improve flame retardant and impact properties.

Benefits of technology

Without destroying the multi-wall carbon nanotube structure, the carboxyl group amount is significantly improved, and the flame retardant and mechanical properties of the material are enhanced, which solves the problems of combustion melting and dropping and material strength reduction, and improves the flame retardant of PET materials. and low temperature impact performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005104932920000051
    Figure BDA0005104932920000051
  • Figure BDA0005104932920000061
    Figure BDA0005104932920000061
  • Figure BDA0005104932920000062
    Figure BDA0005104932920000062
Patent Text Reader

Abstract

The invention discloses a modified multi-walled carbon nanotube, a flame-retardant PET (Polyethylene Terephthalate) material and a preparation method of the flame-retardant PET material. The preparation method of the modified multi-walled carbon nanotube comprises the following steps: S1, mixing a multi-walled carbon nanotube with mixed acid, carrying out ultrasonic oscillation for 15-25 minutes, refluxing for 1-2 hours, diluting with distilled water, filtering, and washing with water until filtrate is neutral; and S2, mixing the product in the step S1 with the mixed solution, refluxing for 1-2 hours, diluting with distilled water, filtering, washing with water until the filtrate is neutral, and drying the filter cake to obtain the modified multi-walled carbon nanotube. According to the prepared modified multi-walled carbon nanotube, the surface carboxyl grafting rate is greatly increased while the structure is maintained. When the flame retardant is applied to a flame-retardant PET material, the flame retardant property and the mechanical property of the PET material can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer material additives, and specifically relates to a modified multi-walled carbon nanotube, a flame-retardant PET material added with the modified multi-walled carbon nanotube, and a corresponding preparation method. Background Art

[0002] Polyethylene terephthalate (PET) has excellent physical and mechanical properties in a wide temperature range, and its operating temperature can reach 120°C. It has excellent electrical insulation properties, and even at high temperature and high frequency, its electrical properties are still good. It has good creep resistance, fatigue resistance, friction resistance, and dimensional stability. It is widely used in the fields of synthetic fibers, engineering plastics, and packaging materials. However, PET is extremely flammable, with a limiting oxygen index of only 21%, and it has severe burning dripping.

[0003] Among the common flame retardants currently used, halogen flame retardants have the advantages of small addition amount and good effect. However, they are banned because they produce a large amount of toxic and corrosive gases during the combustion process, which has adverse effects on the environment. Phosphorus-containing flame retardants are currently considered to be the most effective flame retardants for PET. Phosphorus-based flame retardants decompose phosphoric acid molecules after heating, promote the dehydration and carbonization of PET polymer chains, and form a dense carbon layer on the combustion surface, isolating the air and flame retardant heat transfer. In addition, phosphorus-containing compounds decompose into small molecular PO2, ·PO and ·HPO free radicals at high temperatures. These components react with ·H and ·OH free radicals generated during the combustion process to interrupt the combustion reaction chain and achieve flame retardancy. In addition, phosphorus-containing compounds generate moisture during the combustion process that can dilute combustible gases and take away the heat of combustion, further enhancing the flame retardant effect of phosphorus-based flame retardants.

[0004] However, phosphorus-containing polyester has the problem of molten dripping, which can cause secondary fires. In addition, PET has poor impact resistance, and the introduction of toughening agents will lead to a decrease in material strength, limiting its scope of application.

[0005] Multi-walled carbon nanotubes are common fillers in polymer materials, which can improve the flame retardancy and strength of materials to a certain extent. In the art, one-step acidification is usually used to increase the amount of carboxyl groups on the surface of multi-walled carbon nanotubes, but the amount of carboxyl groups obtained in this way is small, and a long period of ultrasonic vibration is required, which causes the structure of multi-walled carbon nanotubes to be destroyed, affecting the enhancement effect of the mechanical properties of the material. Summary of the invention

[0006] In view of this, the primary purpose of the present invention is to provide a method for preparing modified multi-walled carbon nanotubes. The preparation method, through two-step acid mixing and coordinated process optimization, can significantly increase the carboxyl grafting rate on the surface of multi-walled carbon nanotubes while reducing damage to the multi-walled carbon nanotube structure, thereby improving the flame retardant properties and mechanical properties of the polymer material.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] The first aspect of the present invention provides a method for preparing modified multi-walled carbon nanotubes, comprising the following steps:

[0009] S1. Mix the multi-walled carbon nanotubes with mixed acid, ultrasonically oscillate for 15 min to 25 min, reflux for 1 h to 2 h, dilute with distilled water, filter and wash with water until the filtrate is neutral; the mixed acid is a mixture of 98% sulfuric acid and 68% nitric acid in a volume ratio of (3 to 2): 1;

[0010] S2. Mix the product in step S1 with a mixed solution, reflux for 1 h to 2 h, dilute with distilled water, filter and wash with water until the filtrate is neutral, dry the filter cake to obtain modified multi-walled carbon nanotubes; the mixed solution is 98% concentrated sulfuric acid and 30% H2O2 in a volume ratio of (4 to 2):1.

[0011] Through the above preparation method, multi-walled carbon nanotubes with a high carboxyl content can be obtained without destroying the structure of the multi-walled carbon nanotubes, thereby significantly improving the flame retardant properties and mechanical properties of the material.

[0012] The multi-walled carbon nanotubes described herein may be common types in the art. In some embodiments of the present invention, the multi-walled carbon nanotubes have a diameter of 30 to 80 nm and a length of 10 to 20 micrometers.

[0013] In a further embodiment, the ultrasonic oscillation described in this article uses an ultrasonic power of 30 to 35 W / L, for example, it can be any value among 30 W / L, 31 W / L, 32 W / L, 33 W / L, 34 W / L, and 35 W / L.

[0014] In a further embodiment, the drying described herein is achieved by conventional drying means in the art to dry the filter cake. The specific time and temperature can be adjusted or optimized based on the known methods or well-known means in the present invention according to actual conditions. In some specific implementation cases of the present invention, the drying temperature is 65-85°C and the time is 5-12h; preferably, the drying is 80°C for 10h.

[0015] The modified multi-walled carbon nanotubes prepared by the preparation method of the invention have a carboxyl mass content of 5.5% to 6.3% calculated by the acid-base titration principle.

[0016] The second aspect of the present invention provides the use of the modified multi-walled carbon nanotubes prepared by the preparation method described above in the preparation of flame-retardant PET materials.

[0017] The third aspect of the present invention provides a flame-retardant PET material, which is prepared by weight of 90-100 parts of PET, 6-10 parts of flame retardant, 3-8 parts of toughening agent, 3-8 parts of modified multi-walled carbon nanotubes, 0.3-0.5 parts of antioxidant and 0.1-0.3 parts of lubricant;

[0018] Wherein, the modified multi-walled carbon nanotubes are prepared by the preparation method as described above.

[0019] The present invention adds modified multi-walled carbon nanotubes as an anti-dripping agent into the PET system to improve the flame retardant properties of the PET material. Meanwhile, the modified multi-walled carbon nanotubes have good dispersibility and can cooperate with the toughening agent to improve the impact properties of the PET material, especially the low-temperature impact properties.

[0020] In some specific implementation cases of the present invention, the intrinsic viscosity of the PET is 0.6-1.0 dL / g.

[0021] The flame retardant, antioxidant and lubricant in the present invention can all be common types in the art. In some specific embodiments of the present invention, the flame retardant is at least one of triphenyl phosphate, melamine, melamine polyphosphate, melamine phosphate and piperazine pyrophosphate. The antioxidant is one or a mixture of two of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol, tris(2,4-di-tert-butylphenyl) phosphite and distearyl thiodipropionate, and the lubricant is one of magnesium stearate, zinc stearate and barium stearate.

[0022] Furthermore, the toughening agent in the present invention is at least one of ethylene-methyl acrylate-glycidyl methacrylate copolymer and ethylene-butyl acrylate-glycidyl methacrylate copolymer.

[0023] More preferably, the mass ratio of the modified multi-walled carbon nanotubes to the toughening agent is (1-2):1. Under this ratio, the synergistic effect of the modified multi-walled carbon nanotubes and the toughening agent is most prominent.

[0024] The third aspect of the present invention provides a method for preparing the flame retardant PET material as described above, comprising the following steps:

[0025] Fully mix 90-100 parts of PET, 6-10 parts of flame retardant, 3-8 parts of toughening agent, 3-8 parts of modified multi-walled carbon nanotubes, 0.3-0.5 parts of antioxidant and 0.1-0.3 parts of lubricant according to weight ratio to obtain a uniform mixture;

[0026] The mixed material is processed and formed to obtain a flame-retardant PET material.

[0027] The mixing method adopts a mechanical mixing method known in the art, and the specific conditions can be adjusted as needed. In some specific implementation cases of the present invention, the mixing is performed by a high-speed mixer at a speed of 500-800 r / min for 5-10 minutes.

[0028] The processing and molding described in this article can choose a processing method known in the art according to the type of the final product. In some specific implementation cases of the present invention, extrusion molding is performed by a twin-screw extruder, and the specific processing conditions are determined based on methods known in the art according to different raw materials. In some specific embodiments of the present invention, the processing temperatures of each zone of the twin-screw extruder are: 190-200°C in zone 1, 200-210°C in zone 2, 210-230°C in zone 3, 230-240°C in zone 4, 240-250°C in zone 5, and 250-260°C in zone 6; the screw speed is 300-400rpm.

[0029] Beneficial effects of the present invention:

[0030] The present invention uses a two-step acidification treatment to significantly increase the surface carboxyl content of the modified multi-walled carbon nanotubes in a relatively short time, and the multi-walled carbon nanotube structure is not damaged. The modified multi-walled carbon nanotubes can be used as an anti-dripping agent in PET materials, so that they react with PET molecules during melt blending, increase the viscosity of the melt, promote the combustion of PET into carbon, improve the density of the carbon layer, exert an excellent barrier effect, and solve the dripping phenomenon of the burning melt, thereby improving the flame retardancy of the PET material.

[0031] In addition, the modified multi-walled carbon nanotubes prepared in the present invention have good compatibility with PET, solving the problem of easy agglomeration of nanomaterials, can be evenly dispersed in the PET matrix, and can cooperate with the toughening agent to improve the impact performance of the PET material, especially the excellent low-temperature impact performance, and maintain a high strength. DETAILED DESCRIPTION

[0032] Embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. In addition, unless otherwise specified, methods that do not specifically record conditions or steps are conventional methods, and the reagents and materials used can be obtained from commercial sources.

[0034] Some of the raw material information in the following examples and comparative examples are as follows:

[0035] PET CZ328, Jiangsu Sanfangxiang Group;

[0036] Multi-walled carbon nanotube TF-400, Shandong Tanfeng New Material Technology Co., Ltd.;

[0037] Other additives are conventional commercially available products.

[0038] Example 1

[0039] Preparation of modified multi-walled carbon nanotubes

[0040] S1. Mix multi-walled carbon nanotubes with mixed acid (98% sulfuric acid and 68% nitric acid in a volume ratio of 3:1), ultrasonically oscillate for 15 minutes, reflux for 1 hour, dilute with distilled water, filter with a filter membrane with a pore size of 0.3 microns, and repeatedly wash with deionized water until the filtrate pH = 7.

[0041] S2. Mix the product in step S1 with a mixed solution (98% concentrated sulfuric acid and 30% H2O2 in a volume ratio of 4:1), reflux for 1 hour, dilute with distilled water, filter with a filter membrane with a pore size of 0.3 microns, and repeatedly wash with deionized water until the filtrate pH = 7. The product is placed in a vacuum oven at 80°C and dried for 10 hours.

[0042] Preparation of flame retardant PET materials

[0043] 90 parts of PET, 8 parts of melamine phosphate, 2 parts of piperazine pyrophosphate, 3 parts of modified multi-walled carbon nanotubes, 5 parts of ethylene-butyl acrylate-glycidyl methacrylate copolymer, 0.1 part of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 0.2 part of tris(2,4-di-tert-butylphenyl)phosphite and 0.1 part of magnesium stearate were weighed according to weight parts, and mixed in a high-speed mixer for 10 minutes at a high-speed mixer speed of 500 r / min;

[0044] The uniformly mixed materials are passed through a twin-screw extruder for blending, extrusion, cooling, and pelletizing to obtain a flame-retardant PET material, wherein the processing temperatures of each zone of the twin-screw extruder are: 190° C. in zone 1, 200° C. in zone 2, 210° C. in zone 3, 230° C. in zone 4, 240° C. in zone 5, and 250° C. in zone 6; the screw speed is 300 rpm.

[0045] Comparative Example 1

[0046] The flame retardant PET material in this comparative example was prepared in the same manner as in Example 1, except that no modified multi-walled carbon nanotubes were added. Other steps and process conditions were the same as in Example 1.

[0047] Comparative Example 2

[0048] The preparation of the flame-retardant PET material in this comparative example adopts the same implementation as in Example 1, except that the modified multi-walled carbon nanotubes in Example 1 are replaced with unmodified multi-walled carbon nanotubes of equal weight. Other steps and process conditions are the same as in Example 1.

[0049] Comparative Example 3

[0050] The flame retardant PET material in this comparative example is prepared in the same manner as in Example 1, except that the modified multi-walled carbon nanotubes in Example 1 are replaced with polytetrafluoroethylene in equal weight portions. Other steps and process conditions are the same as in Example 1.

[0051] Comparative Example 4

[0052] The preparation of the flame-retardant PET material in this comparative example adopts the same implementation as in Example 1, except that the modified multi-walled carbon nanotubes are different from those in Example 1. The other steps and process conditions are the same as in Example 1.

[0053] The modified multi-walled carbon nanotubes in this comparative example were prepared by the following method:

[0054] Multi-walled carbon nanotubes were mixed with mixed acid (98% sulfuric acid and 68% nitric acid in a volume ratio of 3:1), ultrasonically oscillated for 15 minutes, refluxed for 2 hours, diluted with distilled water, filtered with a filter membrane with a pore size of 0.3 microns, and repeatedly washed with deionized water until the filtrate pH = 7. The product was placed in a vacuum oven at 80°C and dried for 10 hours.

[0055] Comparative Example 5

[0056] The preparation of the flame-retardant PET material in this comparative example adopts the same implementation as in Example 1, except that the modified multi-walled carbon nanotubes are different from those in Example 1. The other steps and process conditions are the same as in Example 1.

[0057] The modified multi-walled carbon nanotubes in this comparative example were prepared by the following method:

[0058] S1. Mix the multi-walled carbon nanotubes with mixed acid (98% sulfuric acid and 68% nitric acid in a volume ratio of 3:1), subject to ultrasonic oscillation for 1 hour, reflux for 5 hours, dilute with distilled water, filter with a filter membrane with a pore size of 0.3 microns, and repeatedly wash with deionized water until the filtrate has a pH of 7;

[0059] S2. Mix the product of step S1 with a mixed solution (98% concentrated sulfuric acid and 30% H2O2 in a volume ratio of 4:1), reflux for 1 hour, dilute with distilled water, filter with a filter membrane with a pore size of 0.3 microns, and repeatedly wash with deionized water until the filtrate pH = 7. The product is placed in a vacuum oven at 80°C and dried for 10 hours.

[0060] Table 1 Components and dosages of flame retardant PET materials in Example 1 and Comparative Examples 1-5 (parts by weight)

[0061]

[0062]

[0063] Note: a and b in Table 1 respectively indicate that the preparation method of modified multi-walled carbon nanotubes is different from that in Example 1.

[0064] Performance Test 1

[0065] The flame retardant PET materials in Example 1 and Comparative Examples 1-5 were subjected to relevant performance tests according to the following methods:

[0066] (1) Tensile strength: tested according to ASTM D638, tensile rate 50 mm / min;

[0067] (2) Flexural strength: tested according to ASTM D790, with a bending speed of 1.25 mm / min;

[0068] (3) Simply supported beam notched impact strength: tested in accordance with ASTM D6110-18.

[0069] (4) Flame retardant properties: tested in accordance with UL-94 standard, with a specimen thickness of 1.6 mm.

[0070] The test results are shown in Table 2.

[0071] Table 2 Performance test results of flame retardant PET materials in Example 1 and Comparative Examples 1-5

[0072]

[0073] The test results in Table 2 show that the carboxyl grafting rate on the surface of multi-walled carbon nanotubes can be increased in a relatively short time through two-step mixed acid acidification treatment. The modified multi-walled carbon nanotubes can be used as an anti-dripping agent to increase the viscosity of PET, promote the combustion of PET into carbon, improve the density of the carbon layer, play an excellent barrier effect, and improve the dripping phenomenon of the burning melt, thereby improving the flame retardancy of the material.

[0074] Example 2

[0075] Preparation of modified multi-walled carbon nanotubes

[0076] S1. Mix multi-walled carbon nanotubes with mixed acid (98% sulfuric acid and 68% nitric acid in a volume ratio of 2:1), ultrasonically oscillate for 25 minutes, reflux for 2 hours, dilute with distilled water, filter with a filter membrane with a pore size of 0.3 microns, and repeatedly wash with deionized water until the filtrate pH = 7.

[0077] S2. Mix the product in step S1 with a mixed solution (98% concentrated sulfuric acid and 30% H2O2 in a volume ratio of 2:1), reflux for 2 hours, dilute with distilled water, filter with a filter membrane with a pore size of 0.3 microns, and repeatedly wash with deionized water until the filtrate pH = 7. The product is placed in a vacuum oven at 80°C and dried for 10 hours.

[0078] Preparation of flame retardant PET materials

[0079] Weigh 100 parts of PET, 5 parts of triphenyl phosphate, 3 parts of melamine polyphosphate, 6 parts of modified multi-walled carbon nanotubes, 3 parts of ethylene-methyl acrylate-glycidyl methacrylate copolymer, 0.3 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 0.2 parts of distearyl thiodipropionate and 0.1 parts of barium stearate according to weight parts, and mix them in a high-speed mixer for 5 minutes at a high-speed mixer speed of 800 r / min;

[0080] The uniformly mixed materials are passed through a twin-screw extruder for blending, extrusion, cooling, and pelletizing to obtain a flame-retardant PET material, wherein the processing temperatures of each zone of the twin-screw extruder are: 200° C. in zone 1, 210° C. in zone 2, 230° C. in zone 3, 240° C. in zone 4, 250° C. in zone 5, and 260° C. in zone 6; the screw speed is 400 rpm.

[0081] Comparative Example 6

[0082] The flame retardant PET material in this comparative example was prepared in the same manner as in Example 2, except that no modified multi-walled carbon nanotubes were added. Other steps and process conditions were the same as in Example 2.

[0083] Comparative Example 7

[0084] The flame retardant PET material in this comparative example was prepared in the same manner as in Example 2, except that no ethylene-butyl acrylate-glycidyl methacrylate copolymer was added. Other steps and process conditions were the same as in Example 2.

[0085] Comparative Example 8

[0086] The flame retardant PET material in this comparative example is prepared in the same manner as in Example 2, except that the ethylene-methyl acrylate-glycidyl methacrylate copolymer in Example 2 is replaced with an equal weight portion of ethylene-butyl acrylate copolymer. The other steps and process conditions are the same as in Example 2.

[0087] Table 3 Composition and dosage of flame retardant PET materials in Example 2 and Comparative Examples 6-8 (parts by weight)

[0088]

[0089] Performance Test 2

[0090] The flame retardant PET materials in Example 2 and Comparative Examples 6-8 were tested for relevant properties. The results are shown in Table 4. The test items and methods are the same as those in Performance Test 1.

[0091] Table 4 Performance test results of flame retardant PET materials in Example 2 and Comparative Examples 6-8

[0092]

[0093] It can be seen from the test results in Table 4 that the addition of flame retardants will reduce the strength and toughness of the material to a certain extent, and the addition of toughening agents will reduce the strength of the material to a certain extent. The present invention introduces modified multi-walled carbon nanotubes, which not only retain the good structure of multi-walled carbon nanotubes, but also have a higher surface carboxyl grafting rate. When applied to PET materials, while improving the strength of the material, it cooperates with the toughening agent to greatly improve the low-temperature impact performance of the material.

[0094] Example 3

[0095] Preparation of modified multi-walled carbon nanotubes

[0096] S1. Mix multi-walled carbon nanotubes with mixed acid (98% sulfuric acid and 68% nitric acid in a volume ratio of 3:1), ultrasonically oscillate for 20 minutes, reflux for 1 hour, dilute with distilled water, filter with a filter membrane with a pore size of 0.3 microns, and repeatedly wash with deionized water until the filtrate pH = 7.

[0097] S2. Mix the product in step S1 with a mixed solution (98% concentrated sulfuric acid and 30% H2O2 in a volume ratio of 4:1), reflux for 1 hour, dilute with distilled water, filter with a filter membrane with a pore size of 0.3 microns, and repeatedly wash with deionized water until the filtrate pH = 7. The product is placed in a vacuum oven at 80°C and dried for 10 hours.

[0098] Preparation of flame retardant PET materials

[0099] 95 parts of PET, 6 parts of melamine phosphate, 5 parts of modified multi-walled carbon nanotubes, 5 parts of ethylene-butyl acrylate-glycidyl methacrylate copolymer, 0.3 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 0.2 parts of tris(2,4-di-tert-butylphenyl)phosphite and 0.1 parts of barium stearate were weighed according to weight parts, and mixed in a high-speed mixer for 8 minutes at a high speed of 600 r / min;

[0100] The uniformly mixed materials are passed through a twin-screw extruder for blending, extrusion, cooling, and pelletizing to obtain a flame-retardant PET material, wherein the processing temperatures of each zone of the twin-screw extruder are: 200° C. in zone 1, 210° C. in zone 2, 230° C. in zone 3, 240° C. in zone 4, 250° C. in zone 5, and 260° C. in zone 6; the screw speed is 400 rpm.

[0101] Example 4

[0102] Preparation of modified multi-walled carbon nanotubes

[0103] Same as Example 3.

[0104] Preparation of flame retardant PET materials

[0105] 95 parts of PET, 6 parts of piperazine pyrophosphate, 4 parts of modified multi-walled carbon nanotubes, 8 parts of ethylene-butyl acrylate-glycidyl methacrylate copolymer, 0.2 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 0.2 parts of tris(2,4-di-tert-butylphenyl)phosphite and 0.2 parts of zinc stearate were weighed according to weight parts, and mixed in a high-speed mixer for 8 minutes at a high speed of 600 r / min;

[0106] The uniformly mixed materials are passed through a twin-screw extruder for blending, extrusion, cooling, and pelletizing to obtain a flame-retardant PET material, wherein the processing temperatures of each zone of the twin-screw extruder are: 200° C. in zone 1, 210° C. in zone 2, 230° C. in zone 3, 240° C. in zone 4, 250° C. in zone 5, and 260° C. in zone 6; the screw speed is 400 rpm.

[0107] Example 5

[0108] Preparation of modified multi-walled carbon nanotubes

[0109] Same as Example 3.

[0110] Preparation of flame retardant PET materials

[0111] 95 parts of PET, 3 parts of melamine phosphate, 3 parts of piperazine pyrophosphate, 8 parts of modified multi-walled carbon nanotubes, 4 parts of ethylene-butyl acrylate-glycidyl methacrylate copolymer, 0.1 part of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 0.4 part of tris(2,4-di-tert-butylphenyl)phosphite and 0.3 part of zinc stearate were weighed according to weight parts, and mixed in a high-speed mixer for 8 minutes at a high speed of 600 r / min;

[0112] The uniformly mixed materials are passed through a twin-screw extruder for blending, extrusion, cooling, and pelletizing to obtain a flame-retardant PET material, wherein the processing temperatures of each zone of the twin-screw extruder are: 200° C. in zone 1, 210° C. in zone 2, 230° C. in zone 3, 240° C. in zone 4, 250° C. in zone 5, and 260° C. in zone 6; the screw speed is 400 rpm.

[0113] Table 5 Composition and dosage of flame retardant PET material in Example 3-5 (parts by weight)

[0114]

[0115] Performance Test 3

[0116] The flame retardant PET materials in Examples 3-5 were tested for relevant properties. The results are shown in Table 6. The test items and methods are the same as those in Performance Test 1.

[0117] Table 6 Test results of flame retardant PET material properties in Examples 3-5

[0118]

[0119]

[0120] It can be seen from the test results in Table 6 that the modified multi-walled carbon nanotubes in the present invention can significantly improve the flame retardancy of PET materials. In addition, the modified multi-walled carbon nanotubes synergize with the toughening agent to improve the impact performance of PET materials, especially the excellent low-temperature impact performance, and maintain a high strength.

[0121] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0122] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing modified multi-walled carbon nanotubes, characterized in that: The following steps are involved: S1. Mix the multi-walled carbon nanotubes with mixed acid, ultrasonically oscillate for 15 min to 25 min, reflux for 1 h to 2 h, dilute with distilled water, filter and wash with water until the filtrate is neutral; the mixed acid is a mixture of 98% sulfuric acid and 68% nitric acid in a volume ratio of (3 to 2): 1; S2, mixing the product in step S1 with the mixed solution, refluxing for 1 h to 2 h, diluting with distilled water, filtering and washing with water until the filtrate is neutral, drying the filter cake, and obtaining modified multi-walled carbon nanotubes; The mixed solution is 98% concentrated sulfuric acid and 30% H2O2 in a volume ratio of (4-2):1; Preferably, the multi-walled carbon nanotubes have a diameter of 30 to 80 nm and a length of 10 to 20 microns.

2. The method for preparing modified multi-walled carbon nanotubes according to claim 1, characterized in that: In step S1, the ultrasonic power used in the ultrasonic oscillation is 30-35 W / L; And / or, in step S2, the temperature used for drying is 65-85°C.

3. The method for preparing modified multi-walled carbon nanotubes according to any one of claims 1 to 2, characterized in that: In the modified multi-walled carbon nanotubes, the mass content of carboxyl groups is 5.5% to 6.3%.

4. Use of the modified multi-walled carbon nanotubes prepared by the preparation method according to any one of claims 1 to 3 in the preparation of flame-retardant PET materials.

5. A flame retardant PET material, characterized in that: The invention is prepared from 90-100 parts of PET, 6-10 parts of flame retardant, 3-8 parts of toughening agent, 3-8 parts of modified multi-walled carbon nanotube, 0.3-0.5 parts of antioxidant and 0.1-0.3 parts of lubricant according to weight parts; Wherein, the modified multi-walled carbon nanotubes are prepared by the preparation method according to any one of claims 1 to 3; Preferably, the intrinsic viscosity of the PET is 0.6-1.0 dL / g.

6. The flame retardant PET material according to claim 5, characterized in that: The flame retardant is at least one of triphenyl phosphate, melamine, melamine polyphosphate, melamine phosphate and piperazine pyrophosphate.

7. The flame retardant PET material according to claim 5, characterized in that: The toughening agent is at least one of ethylene-butyl acrylate-glycidyl methacrylate copolymer and ethylene-methyl acrylate-glycidyl methacrylate copolymer.

8. The flame retardant PET material according to claim 5, characterized in that: The mass ratio of the modified multi-walled carbon nanotubes to the toughening agent is (1-2):

1.

9. The flame retardant PET material according to claim 5, characterized in that: The antioxidant is one or a mixture of two of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, tris(2,4-di-tert-butylphenyl) phosphite, and distearyl thiodipropionate; And / or, the lubricant is one of magnesium stearate, zinc stearate and barium stearate.

10. A method for preparing a flame retardant PET material according to any one of claims 5 to 9, characterized in that: The following steps are involved: Fully mix 90-100 parts of PET, 6-10 parts of flame retardant, 3-8 parts of toughening agent, 3-8 parts of modified multi-walled carbon nanotubes, 0.3-0.5 parts of antioxidant and 0.1-0.3 parts of lubricant according to weight ratio to obtain a uniform mixture; Processing the mixture into a shape to obtain a flame-retardant PET material; Preferably, the processing and molding is extrusion molding; Preferably, the extrusion molding is carried out by a twin-screw extruder, and the processing temperatures of the zones of the twin-screw extruder are: 190-200°C in zone 1, 200-210°C in zone 2, 210-230°C in zone 3, 230-240°C in zone 4, 240-250°C in zone 5, and 250-260°C in zone 6; And / or, the screw speed is 300-400 rpm.

Citation Information

Cited By

  • Extrusion insulation low-voltage fire-resistant power cable

    CN120473230A